2018
DOI: 10.1109/tuffc.2018.2821159
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Satellite-Based Frequency Transfer at the 10−16 Level

Abstract: Advanced satellite-based frequency transfers by two-way carrier-phase (TWCP) and integer precise point positioning have been performed between the National Institute of Information and Communications Technology and Korea Research Institute of Standards and Science. We confirm that the disagreement between them is less than at an averaging time of several days. In addition, an overseas frequency ratio measurement of Sr and Yb optical lattice clocks was directly performed by TWCP. We achieved an uncertainty at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…A frequency ratio can also be determined directly from optical frequency ratio measurements. From a weighted average of six optical ratio measurements [49][50][51][52][53][54], we determine R avg opt = 1.207 507 039 343 337 768 (60). We therefore determine a loop misclosure of (R abs − R opt )/R = (0.8 ± Were this violation to occur, it might arise due to variation of the fine structure constant, α; the ratio of the light quark mass to the quantum chromodynamics (QCD) scale, X q = m q /Λ QCD ; or the electron-to-proton mass ratio, µ = m e /m p .…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A frequency ratio can also be determined directly from optical frequency ratio measurements. From a weighted average of six optical ratio measurements [49][50][51][52][53][54], we determine R avg opt = 1.207 507 039 343 337 768 (60). We therefore determine a loop misclosure of (R abs − R opt )/R = (0.8 ± Were this violation to occur, it might arise due to variation of the fine structure constant, α; the ratio of the light quark mass to the quantum chromodynamics (QCD) scale, X q = m q /Λ QCD ; or the electron-to-proton mass ratio, µ = m e /m p .…”
Section: Results and Analysismentioning
confidence: 99%
“…Then, this value is added to y avg (AT1−TAI), the average frequency difference between the NIST This good agreement using a very different analysis method demonstrates that the results in the main text are robust against alternative methods of analysis. To tighten the contraints on the possible variations of fundamental constants, we employ a multi-species analysis that can be used to link absolute frequency measurements of [49][50][51][52][53][54] as described in the main text. The ratio is known with a fractional uncertainty of σ stat = 5.6 × 10 −17 .…”
Section: Appendix B: Frequency Connection To Psfsmentioning
confidence: 99%
“…The demonstrated long-term stability floor is comparable to that obtained in the most sophisticated satellite frequency transfer techniques [38], [39], the fiber-optic approach, however, allows obtaining results a hundred times faster. On the other hand, it may be concluded that the cost-effectiveness of using standard DWDM infrastructure is sacrificed by significant stability degradation when compared with a bidirectional transfer in a single fiber.…”
Section: Discussionmentioning
confidence: 68%
“…2) HXI Receiver: At the HXI receiver shown in Fig. 3(b), the received signal r (t) is 4 1 e j (2π(4 f c1 )t+4φ…”
Section: B Impact Of Free-running Dielectric Resonator Oscillatorsmentioning
confidence: 99%